Thursday

April 17, 2014

April 17, 2014

Posted by **confused** on Thursday, May 24, 2007 at 10:46pm.

okay were does the a come in here? do I just write -3a in place of x as i did before?

**Related Questions**

algebra - Given f(x) = 2x - 5, find f(-3a). F(x)= 2(-3a) -5 F(-3a) = 2(3a)-5 = 1...

algebra - Given g(x) = –2x – 1, find g(3a). G(3a)=-2(3a)-1 = -6a-1 = -5 is this ...

Math - Factor each expression 1-9a^2/a+1 times 4x^2-y^2/x+y Here is what I got...

math - x+a=b/3x x= ? i understand that u bring the x to one side but the answer ...

?? - 2a-3 x a+2 --------------- 4a-6 <-ok why does 4a plus 2a^2-3a <3b = ...

Math - Write each expression as the product of two binomials. 1) a^3 - 3a^2 + 3a...

Math(Please Check My Work.) - 3a^3b^2(-a^3b-a^2b^2)=-3a^9b^3-3a^6b^4 *is this ...

algebra - 3(a+2)=4a I multiply 3*a+3*2=4a so 3a+6=4a I added 3a to 4a/ =7a and ...

algebra - 3ax^2 - 27a You can factor that into 3a (x^2 - 9), which also equals ...

maths algebra - 3a-2(2a+4) 3a-2(2a + 4) you multiply the parenthesis by -2, ...